Development and early diagnosis of critical illness myopathy in COVID‐19 associated acute respiratory distress syndrome. Issue 3 (5th April 2022) - Rodriguez, Belén; Branca, Mattia; Gutt‐Will, Marielena; Roth, Marianne; Söll, Nicole; Nansoz, Sandra; Cameron, David R.; Tankisi, Hatice; Tan, S. Veronica; Bostock, Hugh; Raabe, Andreas; Schefold, Joerg C.; et al.
Abstract: Background: The COVID‐19 pandemic has greatly increased the incidence and clinical importance of critical illness myopathy (CIM), because it is one of the most common complications of modern intensive care medicine. Current diagnostic criteria only allow diagnosis of CIM at an advanced stage, so that patients are at risk of being overlooked, especially in early stages. To determine the frequency of CIM and to assess a recently proposed tool for early diagnosis, we have followed a cohort of COVID‐19 patients with acute respiratory distress syndrome and compared the time course of muscle excitability measurements with the definite diagnosis of CIM. Methods: Adult COVID‐19 patients admitted to the Intensive Care Unit of the University Hospital Bern, Switzerland requiring mechanical ventilation were recruited and examined on Days 1, 2, 5, and 10 post‐intubation. Clinical examination, muscle excitability measurements, medication record, and laboratory analyses were performed on all study visits, and additionally nerve conduction studies, electromyography and muscle biopsy on Day 10. Muscle excitability data were compared with a cohort of 31 age‐matched healthy subjects. Diagnosis of definite CIM was made according to the current guidelines and was based on patient history, results of clinical and electrophysiological examinations as well as muscle biopsy. Results: Complete data were available in 31 out of 44 recruited patients (mean [SD] age, 62.4 [9.8] years). Of these, 17 (55%) developed CIM. Muscle excitability measurements on Day 10 discriminated between patients who developed CIM and those who did not, with a diagnostic precision of 90% (AUC 0.908; 95% CI 0.799–1.000; sensitivity 1.000; specificity 0.714). On Days 1 and 2, muscle excitability parameters also discriminated between the two groups with 73% (AUC 0.734; 95% CI 0.550–0.919; sensitivity 0.562; specificity 0.857) and 82% (AUC 0.820; CI 0.652–0.903; sensitivity 0.750; specificity 0.923) diagnostic precision, respectively. All critically ill COVID‐19 patients showed signs of muscle membrane depolarization compared with healthy subjects, but in patients who developed CIM muscle membrane depolarization on Days 1, 2 and 10 was more pronounced than in patients who did not develop CIM. Conclusions: This study reports a 55% prevalence of definite CIM in critically ill COVID‐19 patients. Furthermore, the results confirm that muscle excitability measurements may serve as an alternative method for CIM diagnosis and support its use as a tool for early diagnosis and monitoring the development of CIM.